Wonder Woman to the rescue! - Carbone, Courtney; Doescher, Erik; Marston, William Moulton 1893-1947 (New York Random House, 2016)
Introduces Wonder Woman, an Amazon gifted with powers from the gods to fight evil and save the day
"Wonder Woman created by William Moulton Marston."
English Stories
2
Keywords: Wonder Woman -- (Fictitious character); Superheroes -- Juvenile fiction; Superheroes; Women superheroes; Women superheroes -- Juvenile fiction; Wonder Woman (Fictitious character) -- Juvenile fiction; Superheroes -- Fiction; Wonder Woman (Fictitious character) -- Fiction; Fiction; Juvenile works